X-linked Alport syndrome: natural history in 195 families and genotype- phenotype correlations in males - Jais, Jean Philippe; Knebelmann, Bertrand; Giatras, Iannis; Marchi, Mario DE; Rizzoni, Gianfranco; Renieri, Alessandra; Weber, Manfred; Gross, Oliver; Netzer, Kai-Olaf; Flinter, Frances; Pirson, Yves; Verellen, Christine; et al. (Journal of the American Society of Nephrology, 2000)
Alport syndrome (AS) is a type IV collagen hereditary disease characterized by the association of progressive hematuric nephritis, hearing loss, and, frequently, ocular changes. Mutations in the COL4A5 collagen gene are responsible for the more common X-linked dominant form of the disease. Considerable allelic heterogeneity has been observed. A "European Community Alport Syndrome Concerted Action" has been established to delineate accurately the AS phenotype and to determine genotype-phenotype correlations in a large number of families. Data concerning 329 families, 250 of them with an X-linked transmission, were collected. Characteristics of the 401 male patients belonging to the 195 families with COL4A5 mutation are presented. All male patients were hematuric, and the rate of progression to end-stage renal failure and deafness was mutation-dependent. Large deletions, non-sense mutations, or small mutations changing the reading frame conferred to affected male patients a 90% probability of developing end-stage renal failure before 30 yr of age, whereas the same risk was of 50 and 70%, respectively, in patients with missense or splice site mutation. The risk of developing hearing loss before 30 yr of age was approximately 60% in patients with missense mutations, contrary to 90% for the other types of mutations. The natural history of X-linked AS and correlations with COL4A5 mutations have been established in a large cohort of male patients. These data could be used for further evaluation of therapeutic approaches.
Keywords: mutace; hluchota; dospělí; chromozom X; Basement Membrane; Genotype; Phenotype; Nephritis, Hereditary; dědičná nefritida; Kidney Glomerulus; genetická vazba; chronické selhání ledvin; Adult; genová přestavba; Collagen; glomerulus; lidé; Deafness; kolagen; genotyp; bazální membrána; Mutation; Eye Diseases; transplantace ledvin; Kidney Failure, Chronic; Incidence; Kidney Transplantation; Male; progrese nemoci; incidence; X Chromosome; Genetic Linkage; Disease Progression; oční nemoci; Gene Rearrangement; fenotyp; mužské pohlaví; Humans